Consumer purchase of halal certified product: a quantitative systematic literature review - Muhammad Ashraf, Fauzi (Emerald Insight, 2022)
Purpose: This study aims to review relevant studies concerning consumer purchase of halal-certified products. A total of 35 studies related to the consumer purchasing behavior of halal-certified products in top-tier journals have been identified according to the recommended systematic literature review methodology.